Analisis Regresi Linier Berganda Untuk Memodelkan Faktor yang Mempengaruhi Nilai Penambahan Utang Tahunan Negara Indonesia - Sulantari, Sulantari; Hariadi, Wigid; Putra, Eric Dwi; Anas, Aswar (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
Indonesia is a one of developing country. After 79 years of independence, Indonesia is not yet free from debt. In 2023, Indonesia's total national debt will reach Rp. 8,144.69 trillion. The debt can cause economic problems in many debtor countries. Regression analysis is a statistical analysis that explains the relationship between the dependent variable (Y) and the independent variable (X). The author is interested in analyzing what factors influence the amount of the annual increase in Indonesia's debt. Using multiple linear regression analysis, the results show that the variables that influence the amount of the increase in Indonesia's national is a variable debt are the GDP growth (X1), variable the GDP value 1 year ago (X2), and variable the debt to GDP ratio 1 year ago (X3). The coefficient of determination (R2) value is 0.89, which means that 89% of the increase in Indonesia's national debt is influenced by variables variable debt are the GDP growth, variable the GDP value 1 year ago, and variable the debt to GDP ratio 1 year ago. The regression model formed is: Y = -60.489 (X1) + 0.046 (X2) + 592.738 (X3) + e. Keywords: Weighted Moving Average, WMA, Inflation. Abstrak. Negara Indonesia merupakan salah satu negara berkembang. setelah 79 tahun merdeka, Indonesia belum lepas dari hutang. Tahun 2023, total utang negara Indonesia mencapai Rp. 8.144,69 triliun. Utang dapat menimbulkan permasalahan ekonomi pada banyak negara debitur. Analisis regresi adalah suatu analisa statistika yang menjelaskan hubungan antara variabel terikat (Y) dan variabel bebas (X). penulis tertarik untuk menganlisis faktor apa saja yang mempengaruhi besaran nilai penambahan hutang tahunan negara Indonesia. Menggunakan analsisi regresi linier berganda, diperoleh hasil bahwa Variabel yang berpengaruh terhadap besar penambahan hutang Negara Indonesia adalah variabel pertumbuhan PDB (X1), variabel nilai PDB 1 tahun yang lalu (X2), dan variabel rasio utang terhadap PDB 1 tahun yang lalu (X3). Nilai koefisien determinasi (R2) sebesar 0.89 yang berarti bahwa sebesar 89% besar penambahan hutang Negara Indonesia dipengaruhi oleh variabel X1, X2, dan X3. Model regresi yang terbentuk adalah: Y = -60.489 (X1) + 0.046 (X2) + 592.738 (X3) + e . Kata kunci: Analisis Regresi, Berganda, Utang Indonesia.